The Utilization Premium - Grigoris, Fotis; Segal, Gill (Management Science, 2024)
We study the interaction of flexible capital utilization and depreciation for expected returns and investment of firms. Empirically, an investment strategy that buys (sells) equities with low (high) utilization rates earns 5% per annum. Utilization predicts excess returns beyond other production-based variables. We reconcile this novel utilization premium quantitatively using a production model. The model suggests that flexible utilization is important for matching the cross-sectional distribution of investment and stock prices jointly. A model without flexible utilization yields many counterfactuals that flexible utilization addresses by making depreciation fluctuate endogenously. Overall, utilization tightens the link between firms’ production and valuations. This paper was accepted by Lukas Schmid, finance. Supplemental Material: The data files and online appendix are available at https://doi.org/10.1287/mnsc.2022.4647 .